2011
DOI: 10.1108/00251741111143630
|View full text |Cite
|
Sign up to set email alerts
|

External technology sourcing: evidence from design‐driven innovation

Abstract: PurposeThe purpose of the paper is to analyse the changing of governance modes for the acquisition of external technology in the context of design driven innovation.Design/methodology/approachThis is an explorative study drawing on cases of new product development (NPD) by six design‐oriented Italian firms. In analyzing the cases a longitudinal approach is taken.FindingsThe analysis of the cases shows a similar pattern for technology sourcing during the NPD process, starting with informal networks and ending w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…Technology causes uncertainty in respect of the skills and knowledge required to succeed in using new technology (e.g. Veryzer 1998;Nieto 2004;Ortt & Smits 2006;Carbonell & Rodrı´guez-Escudero 2009;Cantarello et al 2011). Ortt and Smits (2006) have eloquently stated that "technology does not offer itself as ready-made packages, but more as opportunities".…”
Section: Technological Uncertaintymentioning
confidence: 99%
See 2 more Smart Citations
“…Technology causes uncertainty in respect of the skills and knowledge required to succeed in using new technology (e.g. Veryzer 1998;Nieto 2004;Ortt & Smits 2006;Carbonell & Rodrı´guez-Escudero 2009;Cantarello et al 2011). Ortt and Smits (2006) have eloquently stated that "technology does not offer itself as ready-made packages, but more as opportunities".…”
Section: Technological Uncertaintymentioning
confidence: 99%
“…With interaction the social and political aspects of innovation become visible. Cooperation between, and the risk of opportunism on behalf of, the partners involved in innovation increases uncertainty (Cantarello et al 2011). For Arias (1995), Sartorius (2006) and Ortt & Smits (2006), the result is the 'fundamental uncertainty' that arises from the wide variety and high complexity of interactions between different actors with their own interests.…”
Section: Journal Of Management Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Souder and Moenaert [50] have offered a little more accurate categorization and have indentified four sources of innovation uncertainty: consumer, technological, competetive and resource uncertainty. Cantarello et al [51], in turn, have stressed behavioral uncertainty around innovation. Furthermore, Macdonald and Jianling [52] and Halbesleben et al [53], among others, have identified the timing of innovation as a source of uncertainty.…”
Section: Innovation As a Novelty In Action In A State Of Uncertaintymentioning
confidence: 99%
“…Nevertheless, following the example of previous works written by other authors (Hirschheim 2006;Holmström Olsson et al 2008;Kelly and Noonan 2008), both terms will be used indifferently and interchangeably throughout this paper. IS Offshore Outsourcing raises problems similar to those associated with outsourcing inside the same country; it shares the same motivations or reasons which make it attractive and similar risks or potential problems (Cantarello et al 2011). However, the geographical as well as cultural distance which often exists between clients and providers of these services leads to the emergence of several risks which are specific to Offshore Outsourcing, such as those derived from having to battle with various time zones, different legislations or additional security and privacy problems.…”
Section: Introductionmentioning
confidence: 99%